Penetration trajectory of rigid projectile in the heterogeneous meso-scale concrete target. Issue 7 (May 2022) - Zhang, Jie; Wang, Zhiyong; Wang, Zhihua; Shu, Xuefeng; Li, QM
For the normal penetration of a symmetrical rigid projectile into a concrete target with coarse aggregates, the lateral deflection may occur under certain conditions depending on geometrical parameters of the projectile, impact velocity and coarse aggregate distribution. In this work, four dimensionless numbers of projectile, that is, impact factorI ∗, length-to-diameter ratioL / D, nose factorN ∗ and the relative location of mass centerL c / L, are employed to study the effects of projectile parameters on the deflection of penetration trajectory. Numerical studies based on three-dimensional (3D) meso-scale concrete model are conducted and the projectile trajectories are obtained under different dimensionless numbers. According to the development of the deflection angle during the rigid projectile penetration into meso-scale concrete, the motion of the projectile can be divided into four stages, that is, initial deflection, rapid change, deflection rebound and final stage. The numerical results show that, for the same meso-scale concrete target, the deflection of the projectile trajectory becomes larger with the increases ofI ∗, N ∗ andL c / L, while the deflection angle of projectile decreases with the increase ofL / D .